Apply a function to both sides of equality in a Coq hypothesis - coq

The question I have is very similar to the one presented in the link below, but on a hypothesis instead of a goal.
Apply a function to both sides of an equality in Coq?
Say I have the following definition :
Definition make_couple (a:nat) (b:nat) := (a, b).
And the following lemma to prove :
a, b : nat
H : (a, b) = make_couple a b
-------------------------------
(some goal to prove)
I would like to generate the following hypothesis:
new_H : fst (a, b) = fst (make_couple a b)
One way is to write explicitly an assert, then use eapply f_equal :
assert (fst (a, b) = fst (make_couple a b)). eapply f_equal; eauto.
But I would like to avoid, if possible, to write explicitly the assert. I would like to have some tactic or equivalent that would work like this :
apply_in_hypo fst H as new_H
Is there anything in Coq that would come close to that?
Thanks for the answers.

You can use f_equal lemma to do that.
About f_equal.
f_equal : forall (A B : Type) (f : A -> B) (x y : A), x = y -> f x = f y
Arguments A, B, x, y are implicit
Argument scopes are [type_scope type_scope function_scope _ _ _]
f_equal is transparent
Expands to: Constant Coq.Init.Logic.f_equal
Here is how you can apply it to a hypothesis:
Goal forall a b : nat, (a, b) = (a, b) -> True.
intros a b H.
apply (f_equal fst) in H.
The above snippet can be rewritten in a more concise manner using intro-patterns:
Restart.
intros a b H%(f_equal fst).
Abort.

Related

Defining functions inside proof scope

I'm trying to prove that injective functions are left invertible in Coq. I've reached a point in my proof where my goal is an "exists" proposition. I want to define a function that uses terms from proof scope (types and functions I've intro'ed before) and then show the function to the "exists" goal. Here's what I wrote so far:
(* function composition *)
Definition fun_comp {A B C: Type} (f:A -> B) (g:B -> C) : A -> C :=
fun a: A => g (f a).
Notation "g .o f" := (fun_comp f g) (at level 70).
Definition nonempty (A: Type) := exists a: A, a = a.
(* identity function for any given type *)
Definition fun_id (A: Type) := fun a: A => a.
(* left invertible *)
Definition l_invertible {A B: Type} (f: A -> B) :=
exists fl:B->A, fl .o f = fun_id A.
Definition injective {A B: Type} (f: A -> B) :=
forall a a': A, f a = f a' -> a = a'.
(* is a given element in a function's image? *)
Definition elem_in_fun_image {A B: Type} (b: B) (f: A -> B) :=
exists a: A, f a = b.
Theorem injective_is_l_invertible:
forall (A B: Type) (f: A -> B), nonempty A /\ injective f -> l_invertible f.
Proof.
intros A B f H.
destruct H as [Hnempty Hinj].
unfold l_invertible.
unfold nonempty in Hnempty.
destruct Hnempty as [a0].
(* here would go my function definition and invoking "exists myfun" *)
Here's the function I'm trying to define:
Definition fL (b: B) := if elem_in_fun_image b f
then f a
else a0.
Here's what the proof window looks like:
1 subgoal
A : Type
B : Type
f : A -> B
a0 : A
H : a0 = a0
Hinj : injective f
========================= (1 / 1)
exists fl : B -> A, (fl .o f) = fun_id A
How do I do this? I'm very new to Coq so other comments and pointers are welcome.
This definition cannot be performed in the basic logic. You need to add in a few extra axioms:
(* from Coq.Logic.FunctionalExtensionality *)
functional_extensionality : forall A B (f g : A -> B),
(forall x, f x = g x) -> f = g
(* from Coq.Logic.Classical *)
classic : forall P : Prop, P \/ ~ P
(* from Coq.Logic.ClassicalChoice *)
choice : forall (A B : Type) (R : A->B->Prop),
(forall x : A, exists y : B, R x y) ->
exists f : A->B, (forall x : A, R x (f x)).
The goal is to define a relation R that characterizes the left inverse that you want to construct. The existentially quantified f will then be the inverse! You will need the classic axiom to show the precondition of choice, and you will need functional extensionality to show the equation that you want. I'll leave it as an exercise to find out what R needs to be and how to complete the proof.
Your script should start with the following line.
Require Import ClassicalChoice FunctionalEquality.
Because, as suggested by #arthur-azevedo-de-amorim, you will need these axioms.
Then, you should use choice with the relation "R y x" being
"f x = A or there is no element in A such whose image by f is y".
You will need the axiom classic to prove the existential statement that is required by choice:
assert (pointwise : forall y: B, exists x : A,
f x = y \/ (forall x : A f x <> y)).
choice will give you an existential statement for a function that returns the value you want. You only need to say that this function is the right one. You can give a name to that function by typing destruct (choice ... pointwise) (you have to fill in the ...).
You will have to prove an equality between two functions, but using the axiom functional_extensionality, you can reduce this problem to just proving that the two functions are equal on any x.
For that x, just instantiate the characteristic property of the function (as produced by destruct (choice ... pointwise) with the
value f x. There is a disjuction, but the right-hand side case is self-contradictory, because obviously f x is f x for some x.
For the left-hand side case, you will get an hypothesis of the form (I name the function produced by (choice ... pointwise) with the name it:
f (it (f x)) = f x
Here you can apply your injectivity assumption. to deduce that it (f x) = x.
This pretty much spells out the proof. In my own, experiment, I used classic, NNP, not_all_ex_not, functional_extensionality, which are lemmas coming from ClassicalChoice of FunctionalEquality.

Functional extensionality for John Major's equality

Is functional extensionality provable for John Major's equality (possibly relying on safe axioms)?
Goal forall A (P:A->Type) (Q:A->Type)
(f:forall a, P a) (g:forall a, Q a),
(forall a, JMeq (f a) (g a)) -> JMeq f g.
If not, is it safe to assume it as an axiom?
It's provable from usual function extensionality.
Require Import Coq.Logic.FunctionalExtensionality.
Require Import Coq.Logic.JMeq.
Theorem jmeq_funext
A (P : A -> Type) (Q : A -> Type)
(f : forall a, P a)(g : forall a, Q a)
(h : forall a, JMeq (f a) (g a)) : JMeq f g.
Proof.
assert (pq_eq : P = Q).
apply functional_extensionality.
exact (fun a => match (h a) with JMeq_refl => eq_refl end).
induction pq_eq.
assert (fg_eq : f = g).
apply functional_extensionality_dep.
exact (fun a => JMeq_rect (fun ga => f a = ga) eq_refl (h a)).
induction fg_eq.
exact JMeq_refl.
Qed.

Understanding specialize tactic

Trying to comprehend the answer of #keep_learning I walked through this code step by step:
Inductive nostutter {X:Type} : list X -> Prop :=
| ns_nil : nostutter []
| ns_one : forall (x : X), nostutter [x]
| ns_cons: forall (x : X) (h : X) (t : list X), nostutter (h::t) -> x <> h -> nostutter (x::h::t).
Example test_nostutter_4: not (nostutter [3;1;1;4]).
Proof.
intro.
inversion_clear H.
inversion_clear H0.
unfold not in H2.
(* We are here *)
specialize (H2 eq_refl).
apply H2.
Qed.
Here is what we have before excuting specialize
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : 1 = 1 -> False
============================
False
Here is eq Prop whose constructor eq_refl is used in specialize:
Inductive eq (A:Type) (x:A) : A -> Prop :=
eq_refl : x = x :>A
where "x = y :> A" := (#eq A x y) : type_scope.
I can't explain, how this command works:
specialize (H2 eq_refl).
I read about specialize in reference manual, but the explanation there is too broad. As far as I understand it sees that "1 = 1" expression in H2 satisfies eq_refl constructor and therefore eq proposition is True. Then it simplifies the expression:
True -> False => False
And we get
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : False
============================
False
Can somebody provide me a minimal example with explanation of what is specialize doing, so I could freely use it?
Update
Trying to imitate how specialize works using apply I did the following:
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
apply H in a.
This gives:
A : Type
B : Type
H : A -> B
a : B
============================
B
Almost the same as specialize, only different hypothesis name.
In test_nostutter_4 theorem I tried this and it worked:
remember (#eq_refl nat 1) as Heq.
apply H2 in Heq as H3.
It gives us:
H1 : 3 <> 1
H : nostutter [1; 4]
H2 : 1 = 1 -> False
Heq : 1 = 1
H3 : False
HeqHeq : Heq = eq_refl
============================
False
This one was more complex, we had to introduce a new hypothesis Heq. But we got what we need - H3 at the end.
Does specialize internally use something like remember? Or is it possible to solve it with apply but without remember?
specialize, in its simplest form, simply replaces a given hypothesis with that hypothesis applied to some other term.
In this proof,
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
specialize (H a).
exact H.
Qed.
we initially have the hypothesis H: A -> B. When we call specialize (H a), we apply H to a (apply as in function application). This gives us something of type B. specialize then gets rid of the old H for us and replaces it with the result of the application. It gives the new hypothesis the same name: H.
In your case, we have H2: 1 = 1 -> False, which is a function from the type 1 = 1 to the type False. That means that H2 applied to eq_refl is of type False, i.e. H2 eq_refl: False. When we use the tactic specialize (H2 eq_refl)., the old H2 is cleared and replaced by a new term (H2 eq_refl) whose type is False. It keeps the old name H2, though.
specialize is useful when you're sure that you're only going to use a hypothesis once, since it automatically gets rid of the old hypothesis. One disadvantage is that the old name may not fit the meaning of the new hypothesis. However, in your case and in my example, H is a generic enough name that it works either way.
To your update...
specialize is a core tactic defined directly in the ltac plugin. It doesn't use any other tactic internally, since it is its internals.
If you want to keep a hypothesis, you can use the as modifier, which works for both specialize and apply. In the proof
Example specialize {A B: Type} (H: A -> B) (a: A): B.
Proof.
if you do specialize (H a) as H0., instead of clearing H, it'll introduce a new hypothesis H0: B. apply H in a as H0. has the same effect.

Dealing with let-in expressions in current goal

I got stuck while doing some coq proofs around the state monad. Concretely, I've simplified the situation to this proof:
Definition my_call {A B C} (f : A -> B * C) (a : A) : B * C :=
let (b, c) := f a in (b, c).
Lemma mycall_is_call : forall {A B C} (f : A -> B * C) (a : A), my_call f a = f a.
Proof.
intros A B C f a.
unfold my_call.
(* stuck! *)
Abort.
The resulting goal after invoking unfold is (let (b, c) := f a in (b, c)) = f a. If I'm not wrong, both sides of the equality should be exactly the same, but I don't know how to show it from here. Any help?
--
As a side note, I've seen that coq automatically applies the simplification when no product types are involved in the result of the function:
Definition my_call' {A B : Type} (f : A -> B) (a : A) : B :=
let b := f a in b.
Lemma my_call_is_call' : forall A B (f : A -> B) (a : A), my_call' f a = f a.
Proof.
intros A B f a.
unfold my_call'.
reflexivity.
Qed.
It's easy to see what you need to do next, once you recall that
let (b, c) := f a in (b, c)
is syntactic sugar for
match f a with (b, c) => (b, c) end
This means you need to destruct on f a to finish the proof:
Lemma mycall_is_call {A B C} (f : A -> B * C) a :
my_call f a = f a.
Proof.
unfold my_call.
now destruct (f a).
Qed.

apply argument to equal functions in Coq

Suppose I have two functions f and g and I know f = g. Is there a forward reasoning 'function application' tactic that will allow me to add f a = g a to the context for some a in their common domain? In this contrived example, I could use assert (f a = g a) followed by f_equal. But I want to do something like this in more complex situations; e.g.,
Lemma fapp : forall (A B : Type) (P Q : A -> B) (a : A),
(fun (a : A) => P a) = (fun (a : A) => Q a) ->
P a = Q a.
I think I can't correctly infer the general problem that you have, given your description and example.
If you already know H : f = g, you can use that to rewrite H wherever you want to show something about f and g, or just elim H to rewrite everything at once. You don't need to assert a helper theorem and if you do, you'll obviously need something like assert or pose proof.
If that equality is hidden underneath some eta-expansion, like in your example, remove that layer and then proceed as above. Here are two (out of many) possible ways of doing that:
intros A B P Q a H. assert (P = Q) as H0 by apply H. rewrite H0; reflexivity.
This solves your example proof by asserting the equality, then rewriting. Another possibility is to define eta reduction helpers (haven't found predefined ones) and using these. That will be more verbose, but might work in more complex cases.
If you define
Lemma eta_reduce : forall (A B : Type) (f : A -> B),
(fun x => f x) = f.
intros. reflexivity.
Defined.
Tactic Notation "eta" constr(f) "in" ident(H) :=
pattern (fun x => f x) in H;
rewrite -> eta_reduce in H.
you can do the following:
intros A B P Q a H. eta P in H. eta Q in H. rewrite H; reflexivity.
(That notation is a bit of a loose cannon and might rewrite in the wrong places. Don't rely on it and in case of anomalies do the pattern and rewrite manually.)
I don't have a lot of experience with Coq or its tactics, but why not just use an auxiliary theorem?
Theorem fapp': forall (t0 t1: Type) (f0 f1: t0 -> t1),
f0 = f1 -> forall (x0: t0), f0 x0 = f1 x0.
Proof.
intros.
rewrite H.
trivial.
Qed.
Lemma fapp : forall (A B : Type) (P Q : A -> B) (a : A),
(fun (a : A) => P a) = (fun (a : A) => Q a) ->
P a = Q a.
Proof.
intros.
apply fapp' with (x0 := a) in H.
trivial.
Qed.